Situation report on Nepal’s agrifood systems : March 2023 - Kishore, Avinash; Saroj, Sunil; Minot, Nicholas; Dorosh, Paul A.; Parajuli, R.R.; Krupnik, Timothy J. (CSISA, 2023)
As in the previous month, available data suggest Nepal’s agrifood system remained economically stable during March of 2023. Prices largely followed anticipated trends. Despite minor challenges that are likely to have been caused by other factors such as credit access problems for small businesses, no major threats to food or economic security were observed during the last month. Inflation in food and beverage prices is marginally higher than the previous year: The cost of food and beverages increased by 6.2 percent in February 2023 compared to the same period in 2022. This was marginally higher than the 5.6 percent annual inflation in January 2023 and 5.9 percent in December 2022. Cereal prices remain high even after a decent paddy harvest: Annual inflation in the price of cereals and their products increased from 9.6 percent in January 2023 to 12.4 percent in February 2023. This is despite a 7 percent increase domestic paddy production compared to the last year. The continuing embargo on the export of broken rice and quotas on wheat exports by India may contribute to high prices for cereals in Nepal. Rice growers, especially those with larger landholdings who are net sellers of the crop, are likely to gain from high prices. High cereal prices will affect poor households. The average household in Nepal spends one fourth of its food budget on cereal-based products. Poor households spend a larger share of their food budget on cereals. Persistently high prices of cereals will hurt them more. Ongoing liquidity challenges and access to finance: A range of challenges related to lending, purchase of agricultural inputs, purchase of agricultural products, repayment of loans, and were reported during the last month, although they do not appear to be usually intense compared to previous months. Although farmers seem to be on track for maize and vegetable plating in the spring, these issues loom and are could affect farmers’ ability to reliably profit from the upcoming wheat crop and potentially the spring maize and vegetable crops. This could in turn negatively affect loan repayment rates.